2014
DOI: 10.3325/cmj.2014.55.195
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of neurotoxic potential of synthesized polysaccharide-coated and native ferritin-based magnetic nanoparticles

Abstract: AimTo analyze the neurotoxic potential of synthesized magnetite nanoparticles coated by dextran, hydroxyethyl starch, oxidized hydroxyethyl starch, and chitosan, and magnetic nanoparticles combined with ferritin as a native protein.MethodsThe size of nanoparticles was analyzed using photon correlation spectroscopy, their effects on the conductance of planar lipid membrane by planar lipid bilayer technique, membrane potential and acidification of synaptic vesicles by spectrofluorimetry, and glutamate uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…All procedures conformed to the guidelines of the Palladin Institute of Biochemistry. [27][28][29] Before starting the experiments, the protocols were approved by the Animal Care and Use Committee of the Palladin Institute of Biochemistry (Protocol from 19/09-2012).…”
Section: Ethics Statementmentioning
confidence: 99%
“…All procedures conformed to the guidelines of the Palladin Institute of Biochemistry. [27][28][29] Before starting the experiments, the protocols were approved by the Animal Care and Use Committee of the Palladin Institute of Biochemistry (Protocol from 19/09-2012).…”
Section: Ethics Statementmentioning
confidence: 99%
“…Ferritin stores cellular iron in a dynamic manner, allowing the release of the metal according to demand. We found that exogenous ferritin at a concentration of 0.08 mg/ml (iron content 0.7%) demonstrated neuroactive features (Borysov et al 2014 ). The fourth type of nanoparticles included in the comparative analysis is native dust particles derived from ash deposit of fallen volcanic air (JSC-1a, and JSC, Mars-1A from ORBITEC Orbital Technologies Corporation).…”
Section: Discussionmentioning
confidence: 96%
“…Only changes in unspecific glutamate binding to synaptosomes in the presence of JSC-1a were found. Summarizing, carbon dots (Borisova et al 2015 ), detonation nanodiamonds (Pozdnyakova et al 2016 ) and physiological nanocomplex ferritin exhibited neuroactivity at concentrations of 0.08, 0.5 and 0.08 mg/ml, respectively (Borysov et al 2014 ). Whereas, the ability of NaYF 4 :Eu 3+ -PEG and NaYF 4 :Eu 3+ -OH to influence neurotransmitter transport was registered at concentrations starting from 7.5 to 3.5 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane potential was measured using a potentiometric fluorescent dye rhodamine 6G (0.5 µM) based on its potential-mediated binding to the plasma membrane Borysov et al, 2014Kasatkina and Borisova, 2010). The suspension of synaptosomes (0.2 mg ml -1 of final protein concentration) after preincubation at 37 °C for 10 min was added to stirred thermostated cuvette.…”
Section: Measurement Of Synaptosomal Plasma Membrane Potential (E M )mentioning
confidence: 99%